VAŽNOST FUNKCIONALNIH SPOSOBNOSTI I AEROBNOG KAPACITETA KOD STUDENATA KOJI JESU I ONI KOJI NISU PODLOŽENI SPORTSKIM AKTIVNOSTIMA - Hazir Salihu; Vulnet Ameti; Dehari Ibrahim; Špresa Memiši (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
It is ascertained the functional ability position of different students categories. The aerobic capacity at the students that are engaged with daily physical exercises is evidently higher than those that are not doing any physical activities. According to this appears the necessity to be organised different activity for us to the students that would improve their condition about the organization functional ability.